The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/14733140312331384608
|View full text |Cite
|
Sign up to set email alerts
|

Gay men's experiences of therapy

Abstract: Fourteen gay men were interviewed using a structured interview schedule to explore their experiences of being in therapy. Particular importance was given to their perceptions of how their sexual orientation impinged on the counselling process and how their assumptions about counsellor sexual orientation affected the therapeutic relationship. The limitations of using structured interviews in qualitative research are acknowledged. Some significant findings were made, which were not well documented in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…It is thought that internalised homophobic scripts along with the gender of the counsellor may be important variables in understanding countertransference issues. Mair (2003) explored the narratives of gay men, and suggested that homophobia is a significant problem in clients and their counsellors.…”
mentioning
confidence: 99%
“…It is thought that internalised homophobic scripts along with the gender of the counsellor may be important variables in understanding countertransference issues. Mair (2003) explored the narratives of gay men, and suggested that homophobia is a significant problem in clients and their counsellors.…”
mentioning
confidence: 99%
“…For example, Grove (2003) highlights the need for the damaging effects of living in an heterosexist and homophobic society to be understood. Mair (2003), raises the issue of counsellors needing to have a deep understanding of internalised homophobia. Evans (2003) highlights the need for counsellors to "look at their own belief systems more profoundly" (p59).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the persistence of negative therapist attitudes towards gay, lesbian and bisexual clients, recent research has focused on the issues that therapists need to take into consideration when working with lesbians or gay men, for example professional ethics (Evans, 2003), agency policies (Grove, 2003), and specific client needs (Mair, 2003). Important books by Davies and Neal (2000) and Fassinger (2000) have outlined ways of providing a positive and affirming counselling experience to lesbian, gay and bisexual clients.…”
mentioning
confidence: 99%
“…In one study of 24 lesbian clients 92% of respondents stated that they needed to know their counsellor's orientation in order to feel safe (Galgut, 2005) and Moon found 75% of her lesbian respondents were relieved to find lesbian counsellors (Lyndsey Moon, 1994). However Mair found that the majority of gay men in his sample of 14 did not consider the orientation of their therapist to be of importance (Mair, 2003) and Pixton (2003) argues that counsellors of any sexuality should aim to be 'a positive role model for their own sexuality group' (p.214). Hanson (2005) reports that it was therapist skill, or lack of it, that affected client disclosure or non-disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past decade has consistently confirmed that the majority of therapists are ill-equipped to work with LGB clients, having had little training on the topic of sexuality, and often expressing lack of knowledge about such clients (Coyle et al, 1999;Galgut, 1999;Phillips et al, 2001;Evans, 2003;Mair, 2003;Grove, 2009). In 2003, King and McKeown found that a third of gay men, a quarter of bi men and over 40% of lesbian women had negative or mixed reactions from mental health professionals when being open about their sexuality (DOH, 2006).…”
Section: Introductionmentioning
confidence: 99%